Proporsi depresi pada penderita diabetes melitus tipe 2 di RSUP Sanglah Denpasar - Gede Aditya Ersa Krisnawan; Putu Aryani; Komang Ayu Kartika Sari (DiscoverSys Inc., 2019)
Introduction: Over 285 millions of people in 2010 in the world live with diabetes mellitus type 2 (DMT2). In Indonesia based on Riskesdas 2013, 2.45 millions of people live with DMT2 or around 1.5% of Indonesiaâ€™s total population. One of the disease causded by DMT2 is depression. 30% people with DMT2 has also experience depression. Depression in Indonesia based on Riskesdas 2013 has 19 millions of people suffering from it or 11.6% of Indonesiaâ€™s total population.Method: This research was a descriptive study with cross-sectional approach. The subjects was 51 patients diagnosed with diabetes melitus type 2 and did the follow-up in Diabetic Centre of RSUP Sanglah from October-November 2017.Data for this research was acquired Â from interview using Zung Self Depression Scale (ZSDS).Result: The results showed 78.9% sample which experience depression higher in women (80.0%), the unemployeed subject (88.6%), medium educational degree (86.2%), duration of illness >5 years (87.5%), the usage of insulin (81.0%), and patient with complication history (78.8%).Conclusion: Higher depression was found in patients with DMT2 with female gender, not working, disease duration> 5 years, history of insulin use, and had a history of complications. The proportion of depression in DMT2 patient was high, thus further research on relation between depression and DMT2 is necessary to conduct